Mania presenting as a VZV encephalitis in the context of HIV. Issue 9 (7th September 2020) - George, Oliver; Daniel, Jessica; Forsyth, Sophie; Enright, David
Abstract : Acute encephalitis can be life-threatening, especially in the immunocompromised population. Viruses are the main infectious agents, with varicella zoster virus (VZV) a common cause. Neuropsychiatric symptoms are well documented, but it is rare for mania to be the only symptom on presentation. Here, we report a case of hypomania in a 31-year-old white British heterosexual man who following investigation was found to be HIV positive and subsequently diagnosed with VZV encephalitis. To date, we are unaware of any similarly reported cases. It is important to raise awareness of atypical HIV presentations to improve clinical outcomes for patients.